1970
DOI: 10.3329/taj.v22i1.5015
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological Pattern of Haemoptysis in a Tertiary Level Hospital in Bangladesh

Abstract: To identify the causes of haemoptysis and to diagnose the diseases clinically and cost effective laboratory investigations in our situation. Fifty consecutive cases of haemoptysis admitted at Rajshahi Medical College Hospital, Rajshahi during 2000-2001 were prospectively studied .Pulmonary tuberculosis was the commonest found in 19 (38%) cases. Tuberculer bacilli could be isolated in 5 (26.31%) of the cases. Eight (16%) patients were mitral valvular diseases . Bronchial carcinoma was 4(8%) of the series. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The same view is endorsed in several other studies. (1,2,3,4,5,6,7,8,9,10) Like in several studies, we had a male preponderance among the patients presenting with haemoptysis. Shantikumar Singh et al (11) found Paragonimiasis as an important cause of haemoptysis in North-East India.…”
Section: Discussionsupporting
confidence: 78%
“…The same view is endorsed in several other studies. (1,2,3,4,5,6,7,8,9,10) Like in several studies, we had a male preponderance among the patients presenting with haemoptysis. Shantikumar Singh et al (11) found Paragonimiasis as an important cause of haemoptysis in North-East India.…”
Section: Discussionsupporting
confidence: 78%